Assessing North Carolina Pre-K Teachers’ Perceived Preparedness to Work with Chronically Ill Children from Low-Income Communities - Miller, Ashley (East Carolina University, 2022)
Many children within the United States face issues related to chronic illness, including living in impoverished conditions that may exacerbate their health problems and undermine academic success. Given the pervasiveness of childhood chronic illness and poverty, along with their potential impact on children's academic success, it remains important to understand the implications of different chronic illnesses and teachers' perceptions of those conditions, specifically asthma, cancer, and diabetes. This study examined North Carolina Pre-K teachers' perceived preparedness to support children with chronic conditions and/or from low-income families. Using an exploratory mixed-methods approach, 78 NC Pre-K teachers were surveyed to assess their preparedness levels and needed supports within the classroom. The results found that teachers were more prepared and knowledgeable about children from low-income families than children with chronic conditions. Additionally, they were more prepared and knowledgeable about asthma followed by diabetes and then cancer. Educators with more teaching experience were also more prepared to support children with chronic conditions across several different domains. A thematic content analysis of the open-ended responses revealed three major themes: (1) varying sources of support, (2) perceived training effectiveness, and (3) recommendations for professional development opportunities. NC Pre-K teachers serve as vital members of the educational community, working with children under the age of five who have chronic conditions and/or are from low-income families. As such, it remains imperative to improve their preservice education and ongoing professional development to foster higher levels of preparedness to better support diverse populations of students.
Keywords: chronic conditions; poverty; prekindergarten teachers; preparedness; supports; resources; Early childhood educators--North Carolina--Attitudes; Low-income students--North Carolina; Sick children--Education--North Carolina; Chronic diseases in children--North Carolina; Academic achievement